2013
DOI: 10.1001/jamaneurol.2013.2068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis in Neurology

Abstract: In recent years, neurogenetics research had made some remarkable advances owing to the advent of genotyping arrays and next-generation sequencing. These improvements to the technology have allowed us to determine the whole-genome structure and its variation and to examine its effect on phenotype in an unprecedented manner. The identification of rare disease-causing mutations has led to the identification of new biochemical pathways and has facilitated a greater understanding of the etiology of many neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…8 Because complex paediatric neurological disorders are clinically and genetically heterogeneous, it is difficult to prioritize candidate genes. 17 This leads to long diagnostic trajectories with extensive genetic testing, generally without any result. Earlier studies have demonstrated that patients with complex chronic conditions generally have a high utilization of healthcare resources.…”
Section: Discussionmentioning
confidence: 99%
“…8 Because complex paediatric neurological disorders are clinically and genetically heterogeneous, it is difficult to prioritize candidate genes. 17 This leads to long diagnostic trajectories with extensive genetic testing, generally without any result. Earlier studies have demonstrated that patients with complex chronic conditions generally have a high utilization of healthcare resources.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of our study are: (1) The multicenter nature of the study with a systematic and standardized consecutive recruitment; (2) the careful phenotyping applying a standardized and a highly detailed questionnaire and a careful imaging qualitative and quantitative characterization; (3) the application of an innovative genetic strategy using NGS, which permits to identify genetic factors contributing synergistically to SVD susceptibility and to get individual and hidden heritability. 17,31,32 This approach has been previously reported in other two studies on stroke patients. 33,34 The first one by Zhang et al 2014 applied the exome sequencing analysis to a population of 100 Chinese stroke patients and controls, reporting an association with 2 genes with uncertain significance.…”
Section: Discussionmentioning
confidence: 84%
“…Next-generation sequencing technology has revolutionized the discovery of genes responsible for familial neurologic disorders with Mendelian inheritance (Bamshad et al, 2011) and is beginning to successfully define less common and rare variants that contribute to many neurologic diseases with complex genetic inheritance (Pittman and Hardy, 2013). In contrast to GWAS-defined susceptibility loci, sequencing-based approaches are capable of more precisely defining the most likely causal genes and variants when performed in sufficiently large family pedigrees or population samples (Goldstein et al, 2013; MacArthur et al, 2014).…”
Section: Confirming the Functional Impact Of Genetic Variantsmentioning
confidence: 99%